2022
DOI: 10.1101/2022.03.21.485126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-series monitoring of transgenic maize seedlings phenotyping exhibiting glyphosate tolerance

Abstract: Developing herbicide resistant cultivars is one of the effective methods to solve the safety problem caused by the use of herbicide. In this study, hyperspectral image was used to develop more robust leaf chlorophyll content (LCC) prediction model based on different datasets to finally analyze the response of LCC to glyphosate-stress. Chlorophyll a fluorescence (ChlF) was used to dynamically monitor the photosynthetic physiological response of transgenic glyphosate-resistant and wild glyphosate–sensitive maize… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The increase in ABS/RC may be due to a reduced ratio of active RCs and an increase in absorbed light energy, which may be related to the deactivation of RCs or an increase in antenna size. Previous studies ( Tao et al., 2022 ) showed that in general, RCs inactivation of plants is related to photoinhibition, that is, when the amount of light absorbed by plants exceeds the amount of light that can be utilized by their own photosystem, the photosynthetic function of plants decreases. Derks et al.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in ABS/RC may be due to a reduced ratio of active RCs and an increase in absorbed light energy, which may be related to the deactivation of RCs or an increase in antenna size. Previous studies ( Tao et al., 2022 ) showed that in general, RCs inactivation of plants is related to photoinhibition, that is, when the amount of light absorbed by plants exceeds the amount of light that can be utilized by their own photosystem, the photosynthetic function of plants decreases. Derks et al.…”
Section: Discussionmentioning
confidence: 99%